Der Wiener Aktionismus im Kontext des gesellschaftlich-kulturellen Umbruchs der Sechzigerjahre - Nele Gfader (Historia.scribere)
The following pro-seminar-paper deals with the social and cultural tendencies of the sixties. It is less focused on international occurrences than on the very specific characteristics of Austria. In no other country social changes were so much based on cultural disruptions and tendencies which found their unique expression in the Viennese Actionism. The Viennese Actionism was Austria‘s individual contribution to the worldwide revolution of 1968. Therefore this paper shall demonstrate the important role that the (visual) art of the sixties played for Austria.